The Design and Implementation of “Four-in-One” Blended Learning Model in Digital Media Technology Classroom - Xu, Ping; Guan, Yibo (Scholar: Human Sciences, 2020)
In a digitally driven world, many educators are using face-to-face and online methods to improve teaching and learning because of blendedlearning’s availability and convenience. This study serves two purposes. The main purpose of this research was to identify the academic achievement difference between students who studied through “Four-in-One” blended learning model (official website, WeChat official account platform, official Weibo, and cloud database) and students who studied through traditional learning. And second, to investigate the opinions and feedbacks about “Fourin-One” blended learning model. The mixed methods both qualitative and quantitative methods including quasi-experimental research, direct observation and semi-structured interview were applied. The participants were 88 undergraduate students (67 males and 21 females) from a Chinese Computer Application Technology Department. The subjects were selected by purposive sampling and separated into a control group and an experimental group. The data were analyzed by using mean, standard deviation, dependent t-test, and independent t-test. The outcomes of research showed that the experimental group had higher academic achievement scores than the control group. The results of research also revealed that blended learning outcomes related to tailored teaching, technology readiness level, scaffolding learning, and self-regulated learning.